Assessment of seed quality of Indica rice cv. MR297 under accelerated ageing test / Syamsuziati Sidek - Sidek, Syamsuziati (Faculty of Plantation and Agrotechnology, 2019)
The accelerated ageing (AA) was test by using indica rice cv. MR 279 to access quality of the seeds in storage. Determination of seed longevity provides estimation of storage potential of paddy seed. The objectives of study was determine the initial seed moisture content (MC) two weeks after harvest and assessment the potential of seed longevity of MR297. The seed of variety MR297 was obtained from KADA Mulong, Kelantan after two weeks of harvest. Initial seed moisture content (MC) was recorded by placed them in oven for 150˚C for 24 hour. Before conducting AA test, seed MC was maintained at 15% ±0.5 by exposed them to above on temperature room. The AA tests conduct by using 500 seed with 2 replications for each day (0-20 days) and place into incubator with 40˚C. The 0 day replications it must directly put into growth chamber with temperature 32˚C on day and 16˚C at night and it was followed by 5, 10, 15 and 20 days. The result of ability to germinate normally was recorded every 5 days after being placed in growth chamber. The result of initial MC after two weeks harvesting is showed 12.5% and indicated that the seed suitable for storage as the optimum MC for preventing from loss of viability is 10-18%. The mean MC before of AA test was between 14.8-15.3%. AA test of seed longevity resulted in significant decline with the ability to germinate normally (0 day= 94%, 5 day= 94%, 10, 15 and 20 days = 0%). The P50 result showed the longevity of MR297 it about 4 days in 20-25˚C storage.